A hybrid GA-PSO optimization algorithm for conformal antenna array pattern synthesis - Liang, Zhipeng; Ouyang, Jun; Yang, Feng (Journal of electromagnetic waves and applications, 2018)
This paper introduces a hybrid genetic algorithm and particle swarm optimization algorithm (GA-PSO) dedicated to pattern synthesis of conformal antenna arrays. Taking advantages of both methods, the proposed hybrid GA-PSO optimization algorithm has fast convergence speed and high convergence accuracy when applied to antenna array pattern synthesis. To show the performance of the hybrid optimization algorithm, several typical test functions and optimization examples of a linear array pattern synthesis are illustrated. Finally, a 4 × 2 cylindrical conformal microstrip antenna array as a practical synthesis example is studied to demonstrate the proposed algorithm. The simulated and measured results have shown the proposed method is effective and reliable for conformal antenna array pattern synthesis.